Impacts of Bali Tourism Performance Decline due to Covid-19 Pandemic - Dewi, Putu Sri Ronita (Badan Riset dan Inovasi Daerah Provinsi Bali, 2021)
Purpose: Purpose of this research is to identify impact decline of Bali tourism performance due to COVID-19 pandemic. Research method: This research method is descriptive-qualitative. Type of data used is secondary data, such as socio-demographic data, tourism data, economic data, and government policy data. Results and discussion: Decline of Bali’s tourism was preceded by a decrease in tourist visits to Bali due to regulations to physical distancing and restriction on public activities as a prevent the spread of the COVID-19 virus. This has an impact on the aspects of tourism performer income, aspects of employment, and aspects of Bali’s regional income. Implication: The decline in performance of Bali's tourism disrupts various other sectors. The structure of the Bali's economy which is balanced or not only centered on one sector should be tought about.